2010
DOI: 10.4097/kjae.2010.58.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic effect of dexamethasone in reducing postoperative sore throat

Abstract: BackgroundThis study was performed to compare the effectiveness of prophylactic dexamethasone and postintubation dexamethasone in reducing the incidence and severity of postoperative sore throat (POST).MethodsThis was a prospective, randomized, double-blind clinical trial. The study population consisted of 70 patients between 20 and 60 years old who were classified as American Society of Anesthesiologists I-II and were scheduled for elective laparoscopic cholecystectomy. The patients were divided randomly into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 17 publications
1
39
1
1
Order By: Relevance
“…Some studies have demonstrated that preoperative intravenous administration of dexamethasone reduces the incidence of POST significantly. [22][23][24] We used a similar dose of dexamethasone as used in these studies, which may have conflicted with the proposed effect of the lubricants. In our study, however, both groups received the same dose of dexamethasone following intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that preoperative intravenous administration of dexamethasone reduces the incidence of POST significantly. [22][23][24] We used a similar dose of dexamethasone as used in these studies, which may have conflicted with the proposed effect of the lubricants. In our study, however, both groups received the same dose of dexamethasone following intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, POST is resolved spontaneously without specific treatment; however, many patients complain of POST after general anesthesia with endotracheal intubation. Several pharmacological and non-pharmacological trials have been performed to decrease POST [1,[10][11][12][13][14]. Kalil et al [15] reported that preoperative ketamine and aspirin gargle was the most promising pharmacological method for providers practicing in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini berakibat pada timbulnya ketidakpuasan pasien dan terkadang berujung pada claim terhadap rumah sakit. 5,13,[20][21][22] Tingginya insidensi keluhan nyeri tenggorok dan serak pada pasien yang menjalani anestesi umum endotrakeal berdasarkan literatur dan cukup besarnya dampak yang ditimbulkan membangkitkan minat peneliti untuk meneliti mengenai topik ini. Mengingat belum adanya penelitian mengenai hal ini di RSUD Arifin Achmad Pekanbaru, maka peneliti tertarik untuk mengetahui bagaimana gambaran kejadian nyeri tenggorok dan serak pada pasien yang menjalani anestesi umum endotrakeal di RSUD Arifin Achmad Pekanbaru.…”
unclassified